Changing Repertoires and Partisan Ambivalence in the New Brazilian Protests. (16th March 2016) - ALONSO, ANGELA; MISCHE, ANN
Abstract : This article analyses the June 2013 wave of political protests in Brazil, highlighting student movement participation. We make three arguments. First, this was not a single student movement, but a cycle of protest, consisting of many different actors, issues, and forms of demonstration. Second, protesters built what we call hybrid performances, drawing on three repertoires of contention: socialist, autonomist and patriotic. Third, the protests presented a strong rejection of political parties, problematising the relationship between social movements, political parties, and institutional politics.